Small transboundary tributaries of Ferghana Valley, Central Asia: searching for constructive pathways toward cooperation - Holmatov, Bunyod; Lautze, Jonathan; Djumaboev, Kakhramon; Kenjabaev, Shavkat (Frontiers in Water, 2026)
IntroductionCooperation on small transboundary tributaries (STTs) in Ferghana Valley of Central Asia is key to ensuring realization of benefits such as water supply for irrigation and livelihood activities. While factors driving and constraining cooperation on the region’s large rivers has received considerable focus, the dynamics surrounding cooperation at STT level is comparatively ambiguous. In particular, barriers to cooperation have not been systematically identified.ObjectiveTo address this gap, we implemented semi-structured interviews with regional water experts to understand drivers of and constraints to formal cooperation in a set of STTs shared between the Kyrgyz Republic and Uzbekistan in the Ferghana Valley of Central Asia.MethodsPolitical stakeholder analysis tools were employed, with focus placed on water experts and a specific problem– insufficient cooperation on Ferghana Valley STTs, in particular those shared between the Kyrgyz Republic and Uzbekistan. The Kyrgyz-Uzbek STTs were selected for the case study because they account for over 70% of reported STTs in Ferghana Valley.ResultsThe results suggest that expansion of irrigated lands and construction of water infrastructure served as the main drivers of formal cooperation. Main present-day barriers to cooperation relate to border demarcation, lack of political will, low cost of water, and lack of internal (intra-sectoral) coordination. Actors identified as key to enabling formal water cooperation are water and agriculture specialists. Ongoing informal cooperation constitutes a powerful foundation on which to scale up to formal cooperative agreements and should thus form a key part of strategies aimed at realizing cooperation.DiscussionBased on these findings, we propose three concrete recommendations to strengthen cooperation in STTs within the Ferghana Valley: (1) enhance intra-sectoral coordination, planning and information exchange; (2) stimulate appreciation of the benefits of water cooperation in order to enhance political will; and (3) ensure non-water issues such as border delineation are resolved before discussions are initiated; otherwise, water cooperation efforts may be continually undermined.